DASHBOARD SUSTAINABLE DEVELOPMENT GOALS (SDGS) MENGGUNAKAN FRAMEWORK LARAVEL (STUDI KASUS KABUPATEN DAN KOTA PROVINSI LAMPUNG) - Tristiyanto Tristiyanto; Yunda Heningtyas; Aristoteles Aristoteles; Muhammad Yusuf Amran (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2021)
On March 18, 1964, the Province of Lampung was established. In order to carry out efforts to develop Lampung Province, a development framework with a legal foundation and justice in each development process is required. The Sustainable Development Goals (SDGs) are a replacement for the Millennium Development Goals (MDGs), which were established as a result of an agreement amongst 189 leaders of UN member states with the primary goal of improving welfare and community development. As a result of this research, a dashboard was established to track the progress of the SDG indicators. The dashboard produced can analyze, manage, and display the progress of the SDG indicators in a way that all parties can simply read and understand. As a result, everyone at every level of society can understand and guarantee that development is carried out in accordance with the law in order to promote community welfare.